The Effect of Healthy Eating Education on the Knowledge of Mothers - Usi Lanita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The problem of under-five nutrition, especially stunting, is still the focus of the government. Stunting in toddlers can have an impact on physical, mental and emotional development, as well as brain development. Children who suffer from stunting, as adults, will be more susceptible to diseases, both infectious and non-communicable diseases. Jambi Province's stunting prevalence of 13.5% in 2023 has not yet reached the reduction target. Based on SSGI in 2021, the stunting prevalence rate in Jambi City is 14.0%. This study aims to determine the effect of healthy food education on the knowledge of mothers of toddlers. This study is a quasi-experimental study (pre- test and post-test), the respondents were mothers of toddlers in Pinang Merah Village, Jambi City. Data analysis using the Wilcoxon test. The results of the study were an increase in knowledge seen from the results of the pre- test and post-test which statistically proved a significant increase in knowledge (p-value <0.001). It is concluded that there is an effect of healthy food education on the knowledge of mothers of toddlers. It is hoped that local health centers will often carry out counseling or educational activities to the community to increase knowledge, attitudes and behavior so as to increase the degree of public health.